New records of the family Chalcididae (Hymenoptera: Chalcidoidea) from Egypt - Abul-Sood, Medhat I.; Gadallah, Neveen S. (Zootaxa, 2018)
In the present study, a checklist of new records of the family Chalcididae of Egypt is presented based on a total of 180 specimens collected from 24 different Egyptian localities between June 2011 and October 2016, mostly by sweeping and Malaise traps. Nineteen species as well as the subfamily Epitraninae and the genera Bucekia Steffan, Epitranus Walker, Proconura Dodd, and Tanycoryphus Cameron, are newly recorded from Egypt. A single species previously placed in the genus Hockeria is transferred to Euchalcis Dufour as E. rufula (Nikol’skaya, 1960) comb. nov.